2017
DOI: 10.1039/c6sc03847f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of rhamnosylated arginine glycopeptides and determination of the glycosidic linkage in bacterial elongation factor P

Abstract: We describe the synthesis and incorporation of α- and β-configured rhamnosyl arginine cassettes into Pseudomonas aeruginosa elongation factor P-derived glycopeptides. These were used to unequivocally determine the native anomeric configuration of the rhamnose moiety in EF-P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…1B and supplemental Annotations). Although glycosylation events are typically labile under collision-based fragmentation, we observed Arg-GlcNAc to be partially stable, consistent with previous observations of Arg rhamnosylation (29,30). This stability enabled the localization of Arg-GlcNAc to the previously reported sites for FADD (Arg 117 ; Fig.…”
Section: Development Of An Arg-glcnac Immunoenrichment Methodssupporting
confidence: 90%
“…1B and supplemental Annotations). Although glycosylation events are typically labile under collision-based fragmentation, we observed Arg-GlcNAc to be partially stable, consistent with previous observations of Arg rhamnosylation (29,30). This stability enabled the localization of Arg-GlcNAc to the previously reported sites for FADD (Arg 117 ; Fig.…”
Section: Development Of An Arg-glcnac Immunoenrichment Methodssupporting
confidence: 90%
“…The rhamnosylation of Arg32* of EF-P was shown to be performed by EarP, a conserved glycosyltransferase encoded at a position adjacent to efp and employing dTDP-␤-L-rhamnose (TDP-Rha) as the donor substrate (7,21,22). Li et al and Wang et al reported that rhamnose is ␣-linked to Arg32* in bacterial EF-P proteins, demonstrating that EarP inverts the sugar of its donor substrate (27,28). During the preparation of our manuscript, two independent works on the structure of EarP appeared.…”
mentioning
confidence: 99%
“…We and others previously showed that EarP inverts the anomeric configuration on the sugar moiety from TDP-β-L-rhamnose to α-rhamnosyl arginine. [24][25] Reportedly, inverting glycosyltransferases employ a direct displacement SN2-like reaction. 46 The molecular basis for inverted N-linked glycosylation was elucidated for the oligosaccharyl transferase PglB.…”
Section: D13 D17 and E273 Are Involved In Catalysis To Activate The mentioning
confidence: 99%
“…[18][19][20][21] By contrast, activation of a phylogenetically distinct group of EF-Ps encoded in species such as Pseudomonas aeruginosa, or Neisseria meningitidis, depends on rhamnosylation of an arginine R32 EF-P in the equivalent position. 15,[22][23] Rhamnosylation is mediated by the recently discovered glycosyltransferase EarP, which inverts the rhamnosyl moiety of the donor nucleotide sugar dTDP-β-L-rhamnose (TDP-Rha) into α-rhamnosyl-arginine when attached to EF-P. [24][25] Compared to the common and relatively well understood asparagine glycosylation, sugar modifications on the guanidino group of arginine appeared to be rare and almost nothing is known about the molecular mechanism. [26][27] Beside EF-P arginine-glycosylation, to date there are only two further reported cases: The first one described self β-glycosylation of sweet corn amylogenin.…”
mentioning
confidence: 99%